Impact of co-fermentation of Saccharomyces cerevisiae and Pichia kluyveri on the metabolic characteristics of the flavor compounds in mulberry wine - Ding, Bo; Xiong, Ling; Zhao, Shutian; Lin, Ying; Guo, Penghui; Zhang, Wenxue (Frontiers in Nutrition, 2025)
This study investigated the metabolic characteristics of mulberry wine produced by co-fermentation with Saccharomyces cerevisiae (SC) and two different Pichia kluyveri (PK). Although S. cerevisiae inhibited the growth of P. kluyveri during co-fermentation, P. kluyveri showed robust growth adaptability. Classical oenological parameters were not significantly altered by co-fermentation compared to pure-fermentation. The P. kluyveri significantly modulated amino acid metabolism pathways during co-fermentation, enhancing the biosynthesis of higher alcohol acetate compounds. Furthermore, co-fermentation strategy promoted the production of volatile flavor compounds, particularly esters and alcohols, which enriched the wine with distinct floral and fruity flavors. This study provides novel insights into the metabolic mechanisms of co-fermentation with SC and PK strains and highlights the potential of P. kluyveri as a co-fermentation agent for improving the aromatic complexity of fruit wines.